2017
DOI: 10.18551/rjoas.2017-09.41
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Density and Identification of Giant Clams in Coastal Area of Negeri Morella (The District of Leihitu, Central Maluku Regency, Indonesia)

Abstract: Giant clams are protected biota both nationally and internationally. The coastal area of Negeri Morella, the District of Leihitu, Central Maluku Regency, Maluku is one of the areas as the habitat of these giant clams. This study aims to identify the types of clams, conduct ecological studies covering density, diversity index of Tridacninae shells in Central Maluku, especially in Negeri Morella. Implementation of the clam population survey is conducted by using UVC (Underwater Visual Census). The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…This can also be caused by the unstable nature of nitrites. Nitrite is a transitional form of nitrification (ammonia with nitrate) and denitrification (nitrate with nitrogen gas) and is commonly found at low concentrations (Widyasari et al 2016). However, the results also showed that several stations had high nitrite concentrations.…”
Section: Water Qualitymentioning
confidence: 99%
“…This can also be caused by the unstable nature of nitrites. Nitrite is a transitional form of nitrification (ammonia with nitrate) and denitrification (nitrate with nitrogen gas) and is commonly found at low concentrations (Widyasari et al 2016). However, the results also showed that several stations had high nitrite concentrations.…”
Section: Water Qualitymentioning
confidence: 99%
“…Jenis kima yang paling banyak ditemukan di Perairan Desa Sepempang yaitu T. crocea dengan jumlah 200 individu (Gambar 4) pada stasiun III. Hasil tersebut termasuk tinggi apabila dibandingkan dengan penelitian daerah lain, seperti di perairan Pulau Wawosunggu dengan jumlah 39 individu (Hasni et al, 2017), perairan Amdui Distrik Batanta Selatan sebanyak 78 individu (Wakum et al, 2017), Pesisir Morella sebanyak 41 individu (Widyasari et al, 2017), dan Perairan Singapura sebanyak 31 individu (Neo and Todd, 2012 (Calumpong, 1992).…”
Section: Hasil Dan Pembahasanunclassified